2019
DOI: 10.1039/c9ra02412c
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent delivery vehicle containing cobalt oxide–umbelliferone nanoconjugate: DNA/protein interaction studies and anticancer activity on MF7 cancer cell line

Abstract: Model of drug-nanoconjugate with DNA and HSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The fluorescent cobalt oxide (CoO) umbelliferone nanoconjugate having anti-cancer activity can be used both as a drug and carrier. Ali et al have conducted molecular docking studies applying the protein docking program, HEX 8.0.0 using Spherical Polar Fourier Correlations technique to find the binding interactions of the CoO-drug nanoconjugate with the B-DNA dodecamer (also called as Calf thymus DNA (CT-DNA)), a DNA duplex having the sequence (CGCGAATTCGCG) 2 (PDB ID: 1BNA) and human serum albumin (HSA) (PDB ID: 1H9Z) protein separately [ 117 119 ]. The most stable docking results with least binding energies of the CoO-drug nanoconjugate against the DNA molecule and interactions in the binding cavity of the CT-DNA are shown in Fig.…”
Section: Docking In Organic Inorganic and Hybrid Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fluorescent cobalt oxide (CoO) umbelliferone nanoconjugate having anti-cancer activity can be used both as a drug and carrier. Ali et al have conducted molecular docking studies applying the protein docking program, HEX 8.0.0 using Spherical Polar Fourier Correlations technique to find the binding interactions of the CoO-drug nanoconjugate with the B-DNA dodecamer (also called as Calf thymus DNA (CT-DNA)), a DNA duplex having the sequence (CGCGAATTCGCG) 2 (PDB ID: 1BNA) and human serum albumin (HSA) (PDB ID: 1H9Z) protein separately [ 117 119 ]. The most stable docking results with least binding energies of the CoO-drug nanoconjugate against the DNA molecule and interactions in the binding cavity of the CT-DNA are shown in Fig.…”
Section: Docking In Organic Inorganic and Hybrid Systemsmentioning
confidence: 99%
“…
Fig. 18 A Molecular docking complex of calf thymus DNA (CT-DNA) (PDB ID: 1BNA) and cobalt oxide (CoO) umbelliferone drug nanoconjugate using HEX 8.0.0 [ 117 , 118 ]. DNA is represented in carton and surface view.
…”
Section: Docking In Organic Inorganic and Hybrid Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also act as a tumor suppressor and anti-cancer cell metastasis agent. Most studies have shown that umbelliferone reduces the expression of matrix metalloproteinase 9 (Ali et al, 2019; Kandil et al, 2016; Karthikeyan et al, 2016), while decreasing the levels of hyaluronic acid and glucose in the tumor microenvironment and inhibiting tumorigenesis in vitro and in vivo . However, there are no data on umbelliferone’s ability to suppress tumor growth through inhibiting glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…It is now employed as an inhibitor of hyaluronic acid formation and has anti-inflammatory properties. Recent research has demonstrated that umbelliferone has positive effects on breast cancer (Ali et al, 2019; Kandil et al, 2016), patocellular carcinoma (Yu et al, 2015), prostate carcinoma (Shen et al, 2017), oral carcinoma (Vijayalakshmi & Sindhu, 2017), and more. It can also act as a tumor suppressor and anti-cancer cell metastasis agent.…”
Section: Introductionmentioning
confidence: 99%